Haskell too many arguments error - function

I am learning Haskell. I am trying to make a function that deletes integers out of a list when met with the parameters of a certain function f.
deleteif :: [Int] -> (Int -> Bool) -> [Int]
deleteif x f = if x == []
then []
else if head x == f
then deleteif((tail x) f)
else [head x] ++ deleteif((tail x) f)
I get the following errors :
function tail is applied to two arguments
'deleteif' is applied to too few arguments

The issue is that you don't use parentheses to call a function in Haskell. So you just need to use
if f (head x)
then deleteif (tail x) f
else [head x] ++ deleteif (tail x) f

the problem is in deleteif((tail x) f)
it becomes deleteif (tail x f)
so tail gets 2 arguments
and then deleteif a
so deleteif gets 1 argument
you want deleteif (tail x) f
head x == f is wrong you want `f (head x)
you can use pattern matching ,guards and make it more generic
deleteif :: [a] -> (a -> Bool) -> [a]
deleteif [] _ = []
deleteif (x:xs) f
| f x = deleteif xs f
| otherwise = x : deleteif xs f

As already said, deleteif((tail x) f) is parsed as deleteif (tail x f), which means tail is applied to the two arguments x and f, and the result would then be passed on as the single argument to deleteif. What you want is deleteif (tail x) f, which is equivalent to (deleteif (tail x)) f and what most languages1 would write deleteif(tail x, f).
This parsing order may seem confusing initially, but it turns out to be really useful in practice. The general name for the technique is Currying.
For one thing, it allows you to write dense statements without needing many parentheses – in fact deleteif (tail x f) could also be written deleteif $ tail x f.
More importantly, because the arguments don't need to be “encased” in a single tuple, you don't need to supply them all at once but automatically get partial application when you apply to only one argument. For instance, you could use this function like that: deleteif (>4) [1,3,7,5,2,9,7] to yield [7,5,9,7]. This works by partially applying the function2 > to 4, leaving a single-argument function which can be used to filter the list.
1Indeed, this style is possible in Haskell as well: just write the signatures of such multi-argument functions as deleteif :: ([Int], Int->Bool) -> [Int]. Or write uncurry deleteif (tail x, f). But it's definitely better you get used to the curried style!
2Actually, > is an infix which behaves a bit different – you can partially apply it to either side, i.e. you can also write deleteif (4>) [1,3,7,5,2,9,7] to get [1,3,2].

Related

Is there a specific type for mathematical functions in Haskell?

I want to write a function that takes a mathematical function (/,x,+,-), a number to start with and a list of numbers. Then, it's supposed to give back a list.
The first element is the starting number, the second element the value of the starting number plus/minus/times/divided by the first number of the given list. The third element is the result of the previous result plus/minus/times/divided by the second result of the given list, and so on.
I've gotten everything to work if I tell the code which function to use but if I want to let the user input the mathematical function he wants, there are problems with the types. Trying :t (/) for example gives out Fractional a => a -> a -> a, but if you put that at the start of your types, it fails.
Is there a specific type to distinguish these functions (/,x,+,-)? Or is there another way to write this function succesfully?
prefix :: (Fractional a, Num a) => a -> a -> a -> a -> [a] -> [a]
prefix (f) a b = [a] ++ prefix' (f) a b
prefix' :: (Fractional a, Num a) => a -> a -> a -> a -> [a] -> [a]
prefix' (z) x [] = []
prefix' (z) x y = [x z (head y)] ++ prefix' (z) (head (prefix' (z) x y)) (tail y)
A right solution would be something like this:
prefix (-) 0 [1..5]
[0,-1,-3,-6,-10,-15]
Is there a specific type to distinguish these functions (/,*,+,-)?
I don't see a reason to do this. Why is \x y -> x+y considered "better" than \x y -> x + y + 1. Sure adding two numbers is something that most will consider more "pure". But it is strange to restrict yourself to a specific subset of functions. It is also possible that for some function \x y -> f x y - 1 "happens" to be equal to (+), except that the compiler can not determine that.
The type checking will make sure that one can not pass functions that operate on numbers, given the list contains strings, etc. But deliberately restricting this further is not very useful. Why would you prevent programmers to use your function for different purposes?
Or is there another way to write this function succesfully?
What you here describe is the scanl :: (b -> a -> b) -> b -> [a] -> [b] function. If we call scanl with scanl f z [x1, x2, ..., xn], then we obtain a list [z, f z x1, f (f z x1) x2, ...]. scanl can be defined as:
scanl :: (b -> a -> b) -> b -> [a] -> [b]
scanl f = go
where go z [] = [z]
go z (x:xs) = z : go (f z x) xs
We thus first emit the accumulator (that starts with the initial value), and then "update" the accumulator to f z x with z the old accumulator, and x the head of the list, and recurse on the tail of the list.
If you want to restrict to these four operations, just define the type yourself:
data ArithOp = Plus | Minus | Times | Div
as_fun Plus = (+)
as_fun Minus = (-)
as_fun Times = (*)
as_fun Div = (/)

Replacing functions in composite function in haskell

I'm trying to become familiar with Haskell and I was wondering if the following was possible and if so, how?
Say I have a set of functions {f,g,..} for which I was to define a replacement function {f',g',..}. Now say I have a function c which uses these functions (and only these functions) inside itself e.g. c x = g (f x). Is there a way to automatically define c' x = g' (f' x) without explicitly defining it?
EDIT: By a replacement function f' I mean some function that is conceptually relates to f by is altered in some arbitrary way. For example, if f xs ys = (*) <$> xs <*> ys then f' (x:xs) (y:ys) = (x * y):(f' xs ys) etc.
Many thanks,
Ben
If, as seems to be the case with your example, f and f' have the same type etc., then you can easily pass them in as extra parameters. Like
cGen :: ([a] -> [a] -> [a]) -> (([a] -> [a]) -> b) -> [a] -> b
cGen f g x = g (f x)
...which BTW could also be written cGen = (.)...
If you want to group together specific “sets of functions”, you can do that with a “configuration type”
data CConfig a b = CConfig {
f :: [a] -> [a] -> [a]
, g :: ([a] -> [a]) -> b
}
cGen :: CConfig a b -> [a] -> b
cGen (CConfig f g) = f . g
The most concise and reliable way to do something like this would be with RecordWildCards
data Replacer ... = R {f :: ..., g :: ...}
c R{..} x = g (f x)
Your set of functions now is now pulled from the local scope from the record, rather than a global definition, and can be swapped out for a different set of functions at your discretion.
The only way to get closer to what you want would to be to use Template Haskell to parse the source and modify it. Regular Haskell code simply cannot inspect a function in any way - that would violate referential transparency.

Haskell parentheses for function application binding

I'm learning Haskell. I defined the following function (I know I don't need addToList and I can also do Point-free notation I'm just in the process of playing with language concepts):
map :: (a -> b) -> [a] -> [b]
map f [] = []
map f (x:xs) = addToList (f x) map f xs
where
addToList :: a -> [a] -> [a]
addToList x [] = [x]
addToList x xs = x:xs
This produces a compile error:
with actual type `(a0 -> b0) -> [a0] -> [b0]'
Relevant bindings include
f :: a -> b (bound at PlayGround.hs:12:5)
map :: (a -> b) -> [a] -> [b] (bound at PlayGround.hs:11:1)
Probable cause: `map' is applied to too few arguments
In the second argument of `addToList', namely `map'
In the expression: addToList (f x) map f xs
If I put parantheses around map it works:
map :: (a -> b) -> [a] -> [b]
map f [] = []
map f (x:xs) = addToList (f x) (map f xs)
where
addToList :: a -> [a] -> [a]
addToList x [] = [x]
addToList x xs = x:xs
I understand that function application binds more tightly than operators (as discussed in Haskell - too few arguments), however, I don't understand how the compiler would parse the above differently without the parantheses.
The simple way to see that something is wrong is to note that the expression:
addToList (f x) map f xs
is applying 4 arguments to addToList whereas:
addToList (f x) (map f xs)
is applying two arguments to addToList (which is what addToList "expects").
Update
Note that even though map takes two arguments, this expression:
addToList a map c d
is parsed as:
(((addToList a) map) c) d
So here's a possible explanation of what GHC is thinking...
addToList (f x) has type [a] -> [a] - i.e. it is a function which takes a list.
map has type (c -> d) -> [c] -> [d]. It is not a list, but with additional arguments it could produce a list.
So when GHC sees addTolist (f x) map and can't type check it, it sees that if map only had a few more arguments, like this:
addToList (f x) (map ...)
at least the second argument to addToList would be a list - so perhaps that's the problem.
Parsing is a distinct step that is completed before type checking occurs. The expression
addToList (f x) map f xs
has as much meaning to the parser as s1 (s2 s3) s4 s2 s5 has to you. It doesn't know anything about what the names mean. It takes the lexical structure of the string and turns it into a parse tree like
*5
/ \
/ xs
*4
/ \
/ f
*3
/ \
/ map
*2
/ \
addToList *1
/ \
f x
Once the parse tree is complete, then each node is tagged with its type, and type checking can occur. Since function application is denoted simply by juxtaposition, the type checker knows that the left child of a node is a function, the right child is the argument, and the root is the result.
The type checker can proceed roughly as follows, doing an pre-order traversal of the tree. (I'll alter the type signatures slightly to distinguish unrelated type variables until they are unified.)
addToList :: a -> [a] -> [a], so it takes an argument of type a and returns a function of type [a] -> [a]. The value of a is not yet known.
f :: b -> c, so it takes an argument of type b and returns a value of type c. The values of b and c are not yet known.
x has type d. The value of d is not yet known.
Letting b ~ d, f can be applied to x, so *1 :: c
Letting a ~ c, addToList is applied to *1, so *2 :: [a] -> [a]
Uh oh. *2 expects an argument of type [a], but it is being applied to map :: (e -> f) -> [e] -> [f]. The type checker does not know how to unify a list type and a function type, which produces the error you see.

Difference between Monads and Functions

Ok, about Monad, I am aware that there are enough questions having been asked. I am not trying to bother anyone to ask what is monad again.
Actually, I read What is a monad?, it is very helpful. And I feel I am very close to really understand it.
I create this question here is just to describe some of my thoughts on Monad and Function, and hope someone could correct me or confirm it correct.
Some answers in that post let me feel monad is a little bit like function.
Monad takes a type, return a wrapper type (return), also, it can take a type, doing some operations on it and returns a wrapper type (bind).
From my point of view, it is a little bit like function. A function takes something and do some operations and return something.
Then why we even need monad? I think one of the key reasons is that monad provides a better way or pattern for sequential operations on the initial data/type.
For example, we have an initial integer i. In our code, we need to apply 10 functions f1, f2, f3, f4, ..., f10 step by step, i.e., we apply f1 on i first, get a result, and then apply f2 on that result, then we get a new result, then apply f3...
We can do this by functions rawly, just like f1 i |> f2 |> f3.... However, the intermediate results during the steps are not consistent; Also if we have to handle possible failure somewhere in middle, things get ugly. And an Option anyway has to be constructed if we don't want the whole process fail on exceptions. So naturally, monad comes in.
Monad unifies and forces the return types in all steps. This largely simplifies the logic and readability of the code (this is also the purpose of those design patterns, isn't it). Also, it is more bullet proof against error or bug. For example, Option Monad forces every intermediate results to be options and it is very easy to implement the fast fail paradigm.
Like many posts about monad described, monad is a design pattern and a better way to combine functions / steps to build up a process.
Am I understanding it correctly?
It sounds to me like you're discovering the limits of learning by analogy. Monad is precisely defined both as a type class in Haskell and as a algebraic thing in category theory; any comparison using "... like ..." is going to be imprecise and therefore wrong.
So no, since Haskell's monads aren't like functions, since they are 1) implemented as type classes, and 2) intended to be used differently than functions.
This answer is probably unsatisfying; are you looking for intuition? If so, I'd suggest doing lots of examples, and especially reading through LYAH. It's very difficult to get an intuitive understanding of abstract things like monads without having a solid base of examples and experience to fall back on.
Why do we even need monads? This is a good question, and maybe there's more than one question here:
Why do we even need the Monad type class? For the same reason that we need any type class.
Why do we even need the monad concept? Because it's useful. Also, it's not a function, so it can't be replaced by a function. (Your example seems like it does not require a Monad (rather, it needs an Applicative)).
For example, you can implement context-free parser combinators using the Applicative type class. But try implementing a parser for the language consisting of the same string of symbols twice (separated by a space) without Monad, i.e.:
a a -> yes
a b -> no
ab ab -> yes
ab ba -> no
So that's one thing a monad provides: the ability to use previous results to "decide" what to do. Here's another example:
f :: Monad m => m Int -> m [Char]
f m =
m >>= \x ->
if x > 2
then return (replicate x 'a')
else return []
f (Just 1) -->> Just ""
f (Just 3) -->> Just "aaa"
f [1,2,3,4] -->> ["", "", "aaa", "aaaa"]
Monads (and Functors, and Applicative Functors) can be seen as being about "generalized function application": they all create functions of type f a ⟶ f b where not only the "values inside a context", like types a and b, are involved, but also the "context" -- the same type of context -- represented by f.
So "normal" function application involves functions of type (a ⟶ b), "generalized" function application is with functions of type (f a ⟶ f b). Such functions can too be composed under normal function composition, because of the more uniform types structure: f a ⟶ f b ; f b ⟶ f c ==> f a ⟶ f c.
Each of the three creates them in a different way though, starting from different things:
Functors: fmap :: Functor f => (a ⟶ b) ⟶ (f a ⟶ f b)
Applicative Functors: (<*>) :: Applicative f => f (a ⟶ b) ⟶ (f a ⟶ f b)
Monadic Functors: (=<<) :: Monad f => (a ⟶ f b) ⟶ (f a ⟶ f b)
In practice, the difference is in how do we get to use the resulting value-in-context type, seen as denoting some type of computations.
Writing in generalized do notation,
Functors: do { x <- a ; return (g x) } g <$> a -- fmap
Applicative do { x <- a ; y <- b ; return (g x y) } g <$> a <*> b
Functors: (\ x -> g x <$> b ) =<< a
Monadic do { x <- a ; y <- k x ; return (g x y) } (\ x -> g x <$> k x) =<< a
Functors:
And their types,
"liftF1" :: (Functor f) => (a ⟶ b) ⟶ f a ⟶ f b -- fmap
liftA2 :: (Applicative f) => (a ⟶ b ⟶ c) ⟶ f a ⟶ f b ⟶ f c
"liftBind" :: (Monad f) => (a ⟶ b ⟶ c) ⟶ f a ⟶ (a ⟶ f b) ⟶ f c

Agda - Reverse-helper

I'm trying to prove this lema
reverse-++ : ∀{ℓ}{A : Set ℓ}(l1 l2 : 𝕃 A) → reverse (l1 ++ l2) ≡ (reverse l2) ++ (reverse l1)
reverse-++ [] [] = refl
reverse-++ l1 [] rewrite ++[] l1 = refl
reverse-++ l1 (x :: xs) = {!!}
But another function, reverse-helper keeps coming up into my goal and I have no idea how I get rid of it. Any guidance or suggestions?
I'm assuming that in the implementation of reverse, you call reverse-helper. In that case, you probably want to prove a lemma about reverse-helper that you can call in the lemma about reverse. This is a general thing: If you are proving something about a function with a helper function, you usually need a proof with a helper proof, because the induction structure of the proof usually matches the recursion structure of the function.
I think you should start with the different argument.
Since ++ is probably defined with [] ++ a = a, and reverse (x :: xs) = (reverse xs) ++ (x :: nil) it will be better to prove reverse-++ (x :: xs) ys = cong (\xs -> xs ++ (x :: nil)) (reverse-++ xs ys)